Biomass Accumulation, Contaminant Removal, and Settling Performance of Chlorella sp. in Unsterilized and Diluted Anaerobic Digestion Effluent - Canbo Wang; Qi Zhang; Zhiqiang Gu; Longfei Zhang; Rumeng Lu; Cuixia Liu; Yuhuan Liu (Fermentation)
Microalgae demonstrate significant efficacy in wastewater treatment. Anaerobic digestion effluent (ADE) is regarded as an underutilized resource, abundant in carbon, nitrogen, phosphorus, and other nutrients; however, the presence of inhibitory factors restricts microalgal growth, thereby preventing its direct treatment via microalgae. The purpose of this study was to dilute ADE using various dilution media and subsequently cultivate Chlorella sp. to identify optimal culture conditions that enhance microalgal biomass and water quality. The effects of various dilution conditions were assessed by evaluating the biomass, sedimentation properties, and nutrient removal efficiencies of microalgae. The results demonstrate that microalgal biomass increases as the dilution ratio increased. The microalgae biomass in the treatments diluted with simulated wastewater was significantly higher than that with deionized water, but their effluent quality failed to meet discharge standards. The treatment diluted with deionized water for 10 times exhibited abundant microbial biomass with strong antioxidant properties. The corresponding total phosphorus concentration in the effluent (6.96 mg/L) adhered to emission limits under the Livestock and Poultry Industry Pollutant Emission Standards (8 mg/L), while ammonia nitrogen concentration (90 mg/L) was near compliance (80 mg/L). The corresponding microbial biomass, with a sludge volume index (SVI30) of 72.72 mL/g, can be recovered economically and efficiently by simple precipitation. Its high protein (52.07%) and carbohydrate (27.05%) content, coupled with low ash (10.75%), makes it a promising candidate for animal feed and fermentation. This study will aid in understanding microalgal growth in unsterilized ADE and establish a theoretical foundation for cost-effective ADE purification and microalgal biomass production.